A review on plasmonic Au-ZnO heterojunction photocatalysts: Preparation, modifications and related charge carrier dynamics. (April 2019) - Kavitha, R.; Kumar, S. Girish
Abstract: Plasmonic metal-semiconductor hybrid mediated photocatalysis has perceived as a sustainable technology, because of the contribution from each component and to the multifaceted functionalities attained due to the synergistic intra-particle interactions at the interface of integrated components. Due to its intriguing structure-electronic properties, Au-ZnO are intensively investigated for the light induced pollutant degradation and hydrogen evolution under a variety of reaction conditions. The deposition of Au metallic islands induces the visible light response through surface plasmon resonance with concomitant enhancement in the charge carrier separation directly related to the heterojunction formation. In this focused review article, choice of Au over other noble metals, preparative method, band offsets between ZnO and Au, structural configuration of Au-ZnO, photoluminescence studies, morphology induced reactivity, charge carrier dynamics, and mechanisms of photocatalytic reactions associated with Au-ZnO are discussed. An overview of the Au deposition methods provides some insights into the pros and cons of the wide array of techniques used. The significance of molecular linkers in the functionalization of Au or ZnO surface towards achieving the stable composite are also explained. The effective role of Au NPs defining their size-shape-morphology on the ZnO surface together with SPR effects and optimum content in promoting the photocatalytic performance are emphasized. Further advancements in Au-ZnO accomplished by heterostructuring with metals, carbon materials and wide/narrow gap semiconductors are featured by concentrating on the preparation methods and charge carrier dynamics. This review contributes for the modulation of multifunctional Au-ZnO heterostructure concerning the photon harvesting ability, charge carrier separation, interface engineering, and structural stability with their direct implications in energy related fields.